STATE ESTIMATION OF POWER SYSTEMS - MOHAMAD SHUIB, SHAZLINA (Universiti Teknologi PETRONAS, 2007)
State Estimation of Power System has same function as Power Flow Analysis in determining system status which is very important in operating the power systems securely. Detail understanding on the differences between State Estimation and Power Flow Analysis has to be taken into consideration. The focus will be on testing the Power System State Estimation either by using existing software or developed software. The chosen option is to produce software using MA TLAB program that can test the State Estimation in Power System network and in obtaining consistent system states which are magnitude, lVI, and phase angles, tl, of bus voltages. Weight Least Squares Method is used to calculate estimates of the state variables (unknown data) by using measured data. When bad measurements are detected, the estimated states are not reliable anymore. So, the data have to be identified and discarded by statistical tests. The presence of bad data is assumed due to improper connection with reversed positive and negative leads at the meter equipment. The limitations that Power Flow Analysis has can be removed by state estimation based on the weighted least squares method and also the method of detecting and eliminating the bad data.